Identification of intestinal abnormalities in patients with active pulmonary tuberculosis using small bowel capsule endoscopy - Saitou, Miwako; Nemoto, Daiki; Utano, Kenichi; Suzuki, Tomoko; Lefor, Alan Kawarai; Togashi, Kazutomo; Niitsuma, Katsunao (Endoscopy International Open, 2018)
Background and study aims Mycobacterium tuberculosis is often detected in the feces of patients with active pulmonary tuberculosis. However, no study has examined the small intestine using small bowel capsule endoscopy (SBCE). This study aimed to investigate intestinal abnormalities in patients with active pulmonary tuberculosis.Patients and methods SBCE was performed in sputum/feces smear-positive pulmonary tuberculosis patients. From December 2013 to November 2016, 15 patients were enrolled from a dedicated tuberculous ward. The primary outcome was intestinal abnormalities identified by SBCE.Results Fourteen patients (median age 81 years, range 29 – 91; 3 female) underwent SBCE to the terminal ileum. The video was not recorded for one patient who was excluded from the analysis. Intestinal lesions, including 5 annular ulcers in 4 patients, were observed in 64 % (9/14). In subgroup analysis, prevalence tended to be higher in patients undergoing SBCE within 1 month of anti-tuberculous therapy (P = 0.051). Distribution of small intestinal lesions tended to be distal. Four of five annular ulcers were located close to the ileocecal valve.Conclusion Prevalence of intestinal lesions in patients with pulmonary tuberculosis is higher than expected before (UMIN 000017292)